Characterization of Enterococcus Isolates Colonizing the Intestinal Tract of Intensive Care Unit Patients Receiving Selective Digestive Decontamination - Bello Gonzalez, Teresita d. J.; Pham, Phu; Top, Janetta; Willems, Rob J. L.; van Schaik, Willem; van Passel, Mark W. J.; Smidt, Hauke (Frontiers in Microbiology, 2017)
Enterococci have emerged as important opportunistic pathogens in intensive care units (ICUs). In this study, enterococcal population size and Enterococcus isolates colonizing the intestinal tract of ICU patients receiving Selective Digestive Decontamination (SDD) were investigated. All nine patients included in the study showed substantial shifts in the enterococcal 16S rRNA gene copy number in the gut microbiota during the hospitalization period. Furthermore, 41 Enterococcus spp. strains were isolated and characterized from these patients at different time points during and after ICU hospitalization, including E. faecalis (n=13), E. faecium (n=23), and 5 isolates that could not unequivocally assigned to a specific species (E. sp. (n=5)) Multi locus sequence typing revealed a high prevalence of ST 6 in E. faecalis isolates (46%) and ST 117 in E. faecium (52%). Furthermore, antibiotic resistance phenotypes, including macrolide and vancomycin resistance, as well as virulence factor-encoding genes (asa1, esp-fm, esp-fs, hyl and cyl (B)) were investigated in all isolates. Resistance to ampicillin and tetracycline was observed in 25 (61%) and 19 (46%) isolates, respectively. Furthermore, thirty out of 41 isolates harboured the erm (B) gene, mainly present in E. faecium isolates (78%). The most prevalent virulence genes were asa1 in E. faecalis (54%) and esp (esp-fm,74%; esp-fs, 39%). Six out of nine patients developed nosocomial enterococcal infections. however, corresponding clinical isolates were unfortunately not available for further analysis. Our results show that multiple Enterococcus species, carrying several antibiotic resistance and virulence genes, occurred simultaneously in patients receiving SDD therapy, with varying prevalence dynamics over time. Furthermore, simultaneous presence and/or replacement of E. faecium STs was observed, reinforcing the importance of screening multiple isolates to comprehensively characterize enterococcal diversity in ICU patients.